2016
DOI: 10.1039/c6sm01165a
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of red blood cells in microcapillary flow: hydrodynamic versus macromolecule induced interaction

Abstract: We present experiments on RBCs that flow through micro-capillaries under physiological conditions. The strong flow-shape coupling of these deformable objects leads to a rich variety of cluster formation. We show that the RBC clusters form as a subtle imbrication between hydrodynamics interaction and adhesion forces because of plasma proteins, mimicked by the polymer dextran. Clusters form along the capillaries and macromolecule-induced adhesion contribute to their stability. However, at high yet physiological … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…The corresponding cell velocities range from 0.14 mm/s to 10.6 mm/s, covering the whole physiological range in microchannels [60,87,88]. We consider the cells 10 mm away from the channel entrance where most of the cells reached a steady state [35]. Figure 3(a) depicts the fraction of observed shapes as a function of the measured cell velocities, constituting our central result from the experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding cell velocities range from 0.14 mm/s to 10.6 mm/s, covering the whole physiological range in microchannels [60,87,88]. We consider the cells 10 mm away from the channel entrance where most of the cells reached a steady state [35]. Figure 3(a) depicts the fraction of observed shapes as a function of the measured cell velocities, constituting our central result from the experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Quint et al [26] found a stable slipper and a metastable croissant at the same set of parameters in a wider channel of 25 µm × 10 µm. Other publications presenting experiments in channel flow also touch the subject of RBC shapes but focus on other aspects such as the methodology [27][28][29][30][31][32][33][34], dense suspensions and cell interactions [17,21,[34][35][36][37][38][39][40][41] or use vastly larger channel diameters [12,42].…”
Section: Introductionmentioning
confidence: 99%
“…In a quiescent flow, vesicle-vesicle adhesion leads to the formation of vesicle doublets [29,30] or clusters [31][32][33]. As a model for red blood cell (RBC) aggregates, a simplified model for adhesive vesicle-vesicle interactions can reproduce vesicle shapes similar to those observed in experiments of fibrinogen-induced RBC aggregates [31][32][33][34][35][36]. Using the Lennard-Jones (L.-J.)…”
mentioning
confidence: 99%
“…The viscoelastic properties of blood have been examined in early [4][5][6] as well as more recent studies [7,8], illustrating the weaklyattractive suspension nature of blood. The fact that the flow characteristics may play a role on the aggregation of RBCs has been observed in the studies of Tomaiuolo et al [9] and Claveria et al [10], where RBC clustering in microconfined Poiseuille flow is observed independent of aggregative forces. The cluster length was observed to be pressure drop dependent and the formation of larger clusters was favoured by longer residence times in the shear conditions tested [9].…”
Section: Introductionmentioning
confidence: 81%
“…The cluster length was observed to be pressure drop dependent and the formation of larger clusters was favoured by longer residence times in the shear conditions tested [9]. In the study of Clavería et al [10], red blood cell suspensions in physiological buffer solutions (PBS) and in Dextran solutions at different concentrations were used to mimic healthy and pathological levels of fibrinogen in capillary configurations. It was found that there is a strong increase in the number of isolated cells between the low and the high stress flow cases implying more intense aggregation in the low stress cases.…”
Section: Introductionmentioning
confidence: 99%